‘Research Data’ in Social Science Methods - Baral, Uma Nath (Journal of Political Science, 2017)
‘Research Data’ are facts, to be collected in fulfillment of the objectives of the research work. These are gathered through various means of scientific techniques and tools. They may be qualitative or quantitative or mixed form of these, depend more or less on the nature and types of research. We can get required data from primary as firsthand sources and secondary as external sources. There are various ways to collect data; the researcher can adopt the method of observation, interview, questionnaire survey, documentary and other techniques as per the research task and its limitation. Facts gathered through various sources and methods are treated as raw data. When they are refined and edited as per the requirement of research objectives, such accurate and verify data are the information to the research. Information collected from observation of measurement from within an attempt is made to develop generalization or conclusion is treated as research data. Thus, a scientific fact is a conclusion based on the best scientific data available of the moment. Journal of Political Science. Vol. 17, 2017, Page: 82-104